Jawa Furnitur: Sistem Website Penjualan Furnitur Online untuk Meningkatkan Efisiensi dengan Fitur Bertransaksi dan Berinteraksi dengan Pelanggan - Junid Ricco Pratama; Krisnando Duta Dwi Dagdo2; Luqman Anas Naufal; Sendi Farera Adi Gunawan (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This report presents the design and development of a web-based e-commerce platform named "Jawa Furnitur," aimed at addressing various challenges in the furniture sales industry. The background of this project is driven by the growing demand for furniture and the limitations of conventional business models that still rely on offline marketing and manual transactions. These traditional models are no longer sufficient to meet the increasing market needs, thus requiring a more efficient and effective digital solution. In this context, the developed system is designed to facilitate online sales of new furniture, providing an integrated solution that helps sellers manage inventory, process transactions, and expand their market reach. The "Jawa Furnitur" platform is designed with a user-friendly interface, making it easy to use for both sellers and buyers. Efficient product search features, secure payment system integration, and well-managed shipping processes ensure a pleasant shopping experience. This system allows sellers to manage their products in real-time and provide accurate and up-to-date information to customers. By utilizing digital technology, transactions can be processed faster and securely, helping to increase customer satisfaction. The primary goal of developing the "Jawa Furnitur" platform is to improve operational efficiency for sellers, expand market segmentation, and support the B2C (Business to Customer) business model. It is expected that this platform will make a significant contribution to the digital transformation of the furniture retail sector, particularly for SMEs, by providing a practical and systematic means for transacting and interacting with customers. With this platform, small and medium-sized businesses can grow rapidly, introduce their products to a broader market, and accelerate the buying and selling process in the increasingly competitive furniture industry.